2012
DOI: 10.1007/s11270-012-1378-z
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Arsenic Uptake by Leafy Vegetables Grown on Contaminated Soils: Effects of Mineral and Organic Amendments

Abstract: To assess strategies for mitigating Pb and As transfer into leafy vegetables from contaminated garden soils, we conducted greenhouse experiments using two field-contaminated soils amended with materials expected to reduce metal phytoavailability. Lettuce and mustard greens grown on these soils were analysed by ICP-MS, showing that some Pb and As transfer into the vegetables occurred from both soils tested, but plant Pb concentrations were highly variable among treatment replicates. Soil-to-plant transfer was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Research suggests that the uptake of soil lead by vegetable crops may be weak 23,24 . Inhalation or consumption of contaminated soil particles, though, represents another exposure pathway.…”
Section: Hypothesismentioning
confidence: 99%
“…Research suggests that the uptake of soil lead by vegetable crops may be weak 23,24 . Inhalation or consumption of contaminated soil particles, though, represents another exposure pathway.…”
Section: Hypothesismentioning
confidence: 99%
“…Highly variable physical contamination of vegetables (e.g., from dust, soil splash, traffic-related aerial contamination) related to local conditions, and the type of vegetable (with differing surface area and roughness of plants) (McBride et al, 2012; Nali et al, 2009; Säumel et al, 2012; Uzu et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Aluminum (Al) in the vegetables. Al is quite insoluble and unavailable for plant uptake at the near-neutral pH levels generally found in urban garden soils, and its presence in vegetable samples can be taken as an indicator of the physical presence of soil particles either in or on the washed vegetable samples (McBride et al, 2012). For example, washed vegetables were found to contain from 0.07 to 4.88% soil on a dry-weight basis (using immobile soil elements such as Al as indicators of vegetable contamination) (Cary et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic uptake from orchard soils is frequently high enough to cause phytotoxicity in sensitive crops (Bishop and Chisholm 1962; Ross and Crowe 1976). Our own studies of As and Pb uptake from orchard soils by leafy green crops showed that there is a wide range of potential for uptake depending on crop species and the part of the plant analyzed (McBride 2013; McBride et al 2012). Thus, root and leafy crops have a much higher potential for Pb and As contamination than most vegetable fruits.…”
Section: Introductionmentioning
confidence: 99%